2023
DOI: 10.26434/chemrxiv-2023-r0xn7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pyridine-based Strategy towards Nitrogen Isotope Exchange

Minghao Feng,
Maylis Norlöff,
Benoit Guichard
et al.

Abstract: Isotopic labeling is at the core of health and life science applications such as nuclear imaging, pharmacokinetics and bio-distribution studies and plays a central role in drug development. The rapid access to isotopically labeled organic molecules is a sine qua non condition to support these societally vital areas of research. Despite the relevance of pyridine as a biologically active scaffold, the nitrogen-13 labeling of this scaffold remains elusive and an almost prohibited challenge for radio-labelling (+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It is worth noting that other groups concurrently investigated this mode of activation and were able to elegantly engineer its successful utilization for a similar 15 N isotopic labeling strategy. 25,27,28 In parallel, however, after much surveying of activation methods, a modified Zincke-type activation with tosylate 13 (see Scheme 1) proved most effective in our hands across a relatively broad range of azine substrates. 29 Regarding the 15 N surrogate used in the displacement, the simple utilization of 15 NH 4 Cl was considered, as previous researchers had reported its efficacy toward the desired transformation.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…It is worth noting that other groups concurrently investigated this mode of activation and were able to elegantly engineer its successful utilization for a similar 15 N isotopic labeling strategy. 25,27,28 In parallel, however, after much surveying of activation methods, a modified Zincke-type activation with tosylate 13 (see Scheme 1) proved most effective in our hands across a relatively broad range of azine substrates. 29 Regarding the 15 N surrogate used in the displacement, the simple utilization of 15 NH 4 Cl was considered, as previous researchers had reported its efficacy toward the desired transformation.…”
mentioning
confidence: 87%
“…This revealed that, while mildly effective at displacing triflamide, transfer of triflate to the alkyl amine was equally viable, reducing the overall likelihood for high 15 N isotopic enrichment through ANRORC displacement. It is worth noting that other groups concurrently investigated this mode of activation and were able to elegantly engineer its successful utilization for a similar 15 N isotopic labeling strategy. ,, In parallel, however, after much surveying of activation methods, a modified Zincke-type activation with tosylate 13 (see Scheme ) proved most effective in our hands across a relatively broad range of azine substrates …”
mentioning
confidence: 96%
“…Third, deuterating the electron-rich C3- and C5-positions in the Zincke imines prior to ring closure would result in higher mass pyridine isotopologues, which are required for in vivo ADMET studies ( vide infra ). Scheme C shows examples of pyridine isotopologs obtainable via this approach …”
mentioning
confidence: 99%
“…Traditional early stage methods for introducing diverse isotopes often prove time-consuming and resource-intensive, encompassing multiple synthesis steps, harsh conditions, and expensive materials, presenting a significant challenge. However, recent advancements in late-stage approaches, particularly isotope exchange reactions involving hydrogen, carbon, fluorine, nitrogen, and sulfur, now allow for the direct labeling of the desired compound in a single step, effectively addressing challenges inherent in traditional methodologies.…”
mentioning
confidence: 99%